Genetic algorithm-assisted soft fusion-based linear cooperative spectrum sensing - El-Saleh, Ayman A.; Ismail, Mahamod; Ali, Mohd Alaudin Mohd (2011)
In this letter, a cooperative spectrum sensing scheme for cognitive radio networks based on genetic algorithm (GA) is proposed. The proposed scheme lies in optimizing the weighting coefficients vector used in a linear soft-decision fusion-(SDF-) based framework. The detection performance of the proposed GA-assisted SDF-based scheme is compared with the conventional SDF schemes as well as the OR-logic hard-decision fusion (HDF) scheme. The simulation results show that the proposed scheme outperforms all other schemes and can achieve higher probability of detection given the same probability of false alarm.